Wireless backhaul in cellular networks using phased array antenna with optically controlled phase shifter - Jiang, P.; Dubrovka, R.; Donnan, R.; Bigham, J.; Wu, J. (Видавництво Національного університету "Львівська політехніка", 2009)
Introducing relay stations into cellular networks has recently been seen as an effective way to develop high speed wide-area wireless networks since the use of wireless backhaul from relay station to the base station increases the flexibility and cost effectiveness of the deployment. A novel and fast approach to relay station deployment is proposed using phased array antennas and passive direction of arrival. A phased array antenna with electric beam steering ability is used to communicate between the base station and relay station. In this paper, antenna design issues for the phased array antenna to be used by the relay station are described that exploits a new optically controlled phase shifter.
Keywords: antenna arrays; wireless networks; phase shifters; organic semiconductors